Analisis Reject Produk Sayap Pesawat Terbang Komponen Ref D-Nose Panel Menggunakan Metode Statistical Quality Control (SQC) di PT XYZ - Nugraha, Wisnu; Ratik Srimurni, Rafika; Listiani, Evi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The manufacture of aircraft wings is a complex production process that requires high accuracy and precision. Each component must be manufactured to strict standards in order to meet the expected safety and quality criteria. One of the problems that often arise in the production process is component reject, where the component does not meet the set quality standards and must be discarded. The Ref D-Nose Panel component is a very important part in the manufacture of aircraft wings. This section serves as a protector and stabilizer on the nose of the aircraft wing. Therefore, the quality and accuracy of the manufacture and installation of these components is very important to ensure the safety and quality of the aircraft. During the manufacture of Ref D-Nose components, it was possible for these components to become damaged. Defects in the D-nose plate components can affect the quality and performance of the aircraft and even endanger the safety of passengers. The Importance of Reject Analysis for the Aviation Industry, which is included in a high-risk industry, is one of the things that is very influential for the quality of a product, so that there is no loss that must be compensated by the PT for consumers due to the occurrence of rejects. This loss is because the cost of making a component is very large and if the component is not in accordance with the wishes of the consumer, the consumer does not want to accept the component so that the loss is borne by the company. The research was conducted only by using Pareto Charts. The application of the Pareto Diagram is expected to be able to reduce the defect rate so that the quality of the company can increase. , eight types of defects were identified in the Ref D-Nose Panel component consisting of pitting corrosion defects on the surface area, corrosion toolmarks, scratches on marking areas, corrosion toolmarks, damagers, damaged parts/materials, diameter damage, False Cut errors in the chemical mill area , additional hole diameter on the countersunk area, and Actual contour part.